Product Gaussian Quadrature on Circular Lunes. Issue 2 (May 2014) - Fies, Gaspare Da; Vianello, Marco
Abstract: Resorting to recent results on subperiodic trigonometric quadrature, we provide three product Gaussian quadrature formulas exact on algebraic polynomials of degree n on circular lunes. The first works on any lune, and has cardinality. The other two have restrictions on the lune angular intervals, but their cardinality is